PERSEPSI DAN MOTIVASI GENERASI MUDA UNTUK BERPROFESI SEBAGAI PETANI KOPI DI DESA RIGIS JAYA KABUPATEN LAMPUNG BARAT - Thoriqsyah, Hafidz; Bakti, Dadang Karya; Subagja, Ghia (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2025)
Coffee farmers play a crucial role in the coffee industry, but the demographic of coffee farmers in the area tends to be aging. Therefore, a deep understanding of the perceptions and motivations of the younger generation towards the profession of coffee farming is essential to promote the sustainability of the coffee industry in the region. This study explain about analyze the perceptions and motivations of the younger generation in choosing a profession as coffee farmers in Rigis Jaya Village, West Lampung Regency. The research methodology employed qualitative and data collection through interviews administered to the younger generation interested in becoming coffee farmers in Rigis Jaya Village. The findings of the study reveal that the younger generation holds positive perceptions of the coffee farming profession. They recognize its economic potential and environmental sustainability. This research has significant implications for local governments and relevant stakeholders in developing programs and policies that support the development of the younger generation in the field of coffee farming.